Application of a tooth-surface coating material containing pre-reacted glass-ionomer fillers for caries prevention. Issue 3 (December 2015) - Suzuki, Mayu; Yamada, Aya; Saito, Kan; Hino, Ryoko; Sugawara, Yu; Ono, Mariko; Naruse, Masahiro; Arakaki, Makiko; Fukumoto, Satoshi
Abstract: Purpose: Several methods have been used to prevent dental caries, including fluoride application to strengthen teeth and promote remineralization and the use of sealants to fill pits and fissures in pediatric dentistry. However, none of these methods alone can be considered a perfect preventive treatment. For caries prevention, we evaluated pre-reacted glass-ionomer (PRG) Barrier Coat (Shofu Inc., Kyoto, Japan), a tooth-surface coating material developed using PRG technology that contains high levels of controlled-release fluoride. Methods: The tooth-surface coating material was applied clinically as a new method of preventing dental caries. Its effect on plaque adhesion, along with its preventive effect on dental caries was investigated in actual cases treated in a pediatric dentistry department of a university hospital. Results: PRG Barrier Coat was shown to have suitable adhesive strength and to be a safe material that does not fracture the adherend. Actual ion release and acid buffering were confirmed, and when clinically applied, continuous fluoride release and recharge occurred, as did the release of the other ions. This suggests that this material promoted dentin remineralization, suppressed plaque adherence, and had a preventive effect on dental caries. Conclusion: This material promoted enamel remineralization, suppressed plaque adherence, and had a preventive effect on dental caries. These results suggest that this coating material is appropriate for young children at high risk of dental caries.